A carnitine transporter at the blood–brain barrier modulates sleep via glial lipid metabolism in Drosophila - Ashley Avila; Ava S. Lewandowski; Yongjun Li; Jesse Gui; Kaeun A. Lee; Zhenglang Yang; Mari Kim; James T. Lyles; Kai Man; Amita Sehgal; Joshua D. Chandler; Shirley L. Zhang (Proceedings of the National Academy of Sciences, 2025)
To regulate brain function, peripheral compounds must traverse the blood–brain barrier (BBB), an interface between the brain and the circulatory system. To determine whether specific transport mechanisms are relevant for sleep, we conducted a BBB-specific inducible RNAi knockdown (iKD) screen for genes affecting sleep in Drosophila . We observed reduced sleep with knockdown of solute carrier CG6126 , a carnitine transporter, as determined by isotope flux. Our findings suggest that CG6126 regulation of sleep is through the role of the carnitine shuttle in regulating fatty acid metabolism as lipid droplets accumulate in the brains of CG6126 BBB iKD flies. Knocking down mitochondrial carnitine transferases in non-BBB glial cells mimicked the reduced sleep of the CG6126 BBB iKD flies, while bypassing the necessity of carnitine transport with dietary medium-chain fatty acids or palmitoylcarnitine rescued sleep. We propose that carnitine transport via CG6126 promotes brain fatty acid metabolism necessary for maintaining sleep.